2009
DOI: 10.1149/1.3046112
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Local Corrosion Kinetics on Hyper-Stoichiometric UO[sub 2+x] by Scanning Electrochemical Microscopy

Abstract: A method has been developed to determine cathodic reaction rates and the corrosion kinetics at individual substrate UnormalO2+x grains on the micrometer scale using scanning electrochemical microscopy measurements. By fitting experimental probe approach curves to numerically simulated curves, “standard” rate constants for the cathodic reduction reaction on the UnormalO2+x grains are determined. Because the cathodic reduction is coupled to the anodic behavior of the UnormalO2+x at the corrosion potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 66 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…However, the presence of such clusters is associated with a much higher anodic reactivity than observed on the 1.5 at% SIMFUEL used in this study. 52,53 The previous study with SIMFUELs showed that this peak at 640 cm −1 increased in relative intensity while that for the peak at 540 cm −1 decreased 6 as the degree of simulated burn-up (increase in doping level) was increased. This decrease in relative intensity of the 540 cm −1 peak suggests the number, or at least the relative importance, of RE III -O V clusters, is decreasing despite the increase in RE III content.…”
Section: Discussionmentioning
confidence: 90%
“…However, the presence of such clusters is associated with a much higher anodic reactivity than observed on the 1.5 at% SIMFUEL used in this study. 52,53 The previous study with SIMFUELs showed that this peak at 640 cm −1 increased in relative intensity while that for the peak at 540 cm −1 decreased 6 as the degree of simulated burn-up (increase in doping level) was increased. This decrease in relative intensity of the 540 cm −1 peak suggests the number, or at least the relative importance, of RE III -O V clusters, is decreasing despite the increase in RE III content.…”
Section: Discussionmentioning
confidence: 90%
“…1 Solubility and dissolution of uranium oxide in aqueous environment strongly depends on uranium valence state, as U(VI) is more soluble than U(IV) by many orders of magnitude. 6 Hence, the degree of nonstoichiometry in spent nuclear fuel has an important effect on its solubility and corrosion rate 7 which governs the release rate of the majority of radionuclides. 8 This work considers the explicit effect of radiation damage by fission fragments on nonstoichiometry in spent nuclear fuel and outlines a methodology developed for determining the degree of non-stoichiometry in UO 2+x .…”
Section: Introductionmentioning
confidence: 99%
“…ABSTRACT: XPS determination of the oxygen coefficient k O =2+x and ionic (U 4+ , U 5+ and U 6+ ) composition of oxides UO 2+x formed on the surfaces of differently oriented (hkl) planes of thin UO 2 films on LSAT (Al 10 La 3 O 51 Sr 14 Ta 7 ) and YSZ (yttria-stabilized zirconia) substrates was performed. The U 4f and O 1s core-electron peak intensities as well as the U 5f relative intensity before and after the 129 Xe 23+ and 238 U 31+ irradiations were employed.…”
mentioning
confidence: 99%
“…The excess oxygen atoms in hyperstoichiometric uranium dioxide (UO 2+x ) occur as interstitial defects34567891011. Positions and dynamics of these excess oxygen atoms control many important properties, such as thermal conductivity121314, fission-product accommodation and transport15, micro-structure evolution1617, and corrosion behavior1819. These properties are closely related to the performance of the fuel in a reactor and its behavior in a geologic disposal.…”
mentioning
confidence: 99%